FINANCIAL RATIOS AFFECTING FIRM VALUE AND CORPORATE GOVERNANCE AS MODERATING VARIABLE - Abeputri , Audrie; Handojo, Irwanto (E-Jurnal Akuntansi TSM, 2024)
The goal of this research is to gather the empirical data regarding the influence of financial performance, leverage, board of commissioner, sales growth, firm size, liquidity, and dividend policy on firm value. Moreover, corporate governance moderates the impact of financial performance on firm value. The non-financial company used in this research is the consumer cyclicals and non-cyclicals companies with total 43 companies listed on the Indonesia Stock Exchange from 2020 to 2022. The hypothesis testing method used is multiple regression method that resulting financial performance, board of commissioner, sales growth, firm size, and liquidity impact the value of a firm. Strong financial performance will attract investors to invest in company, which will grow stock price. Independent commissioner monitors company’s financial statement that is align with company’s real condition, so it increases investor’s trust as well as firm value. Higher sales growth, the lower firm value due to higher tax expense and production cost. Higher total asset causes lack of efficiency in supervising operational activities and strategies by management. Greater current assets, reflect higher current ratio, have lower return than fixed assets. Therefore, the firm value will decrease. Corporate governance negatively moderates the influence of financial performance on firm value. In decision-making, investors consider high managerial ownership due to opportunistic management’s propensity. Meanwhile, leverage and dividend policy have no impact on firm value.